1996
DOI: 10.1104/pp.112.4.1617
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of L-Phenylalanine Ammonia-Lyase in Transgenic Tobacco Plants Reveals Control Points for Flux into Phenylpropanoid Biosynthesis

Abstract: The phenylpropanoid pathway is responsible for the synthesis of a large range of natural products in plants, including flavonoids (pigments and UV protectants), the structural polymer lignin, and antimicrobial furanocoumarin and isoflavonoid phytoalexins (Hahlbrock and Scheel, 1989; Dixon and Paiva, 1995). Salicylic acid, which is involved in the establishment of both local and systemic plant defense responses, is also a product of this pathway (Klessig and Malamy, 1994). Although the importance of phenylprop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
171
0
2

Year Published

1997
1997
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 215 publications
(181 citation statements)
references
References 39 publications
8
171
0
2
Order By: Relevance
“…The induction of phenolic compounds by stress might also involve changes in enzymes of speciflc branch pathways, as suggested b}^ Dixon & Paiva (1995) and Howies et al (1996). Therefore, plant secondary metabolism might respond to enhanced u.v.-radiation by increased synthesis of those compounds that are most effective as u.v.-protectants at the expense of those that either absorb u.v.-B radiation poorly or are weak antioxidants.…”
Section: Resultsmentioning
confidence: 99%
“…The induction of phenolic compounds by stress might also involve changes in enzymes of speciflc branch pathways, as suggested b}^ Dixon & Paiva (1995) and Howies et al (1996). Therefore, plant secondary metabolism might respond to enhanced u.v.-radiation by increased synthesis of those compounds that are most effective as u.v.-protectants at the expense of those that either absorb u.v.-B radiation poorly or are weak antioxidants.…”
Section: Resultsmentioning
confidence: 99%
“…Although PAL catalyzes the first step in phenylpropanoid biosynthesis and plays a major role in regulating carbon flow into the pathway (Bate et al, 1994), additional flux control points occur at various downstream branches (Howles et al, 1996). Superimposed on regulation of the individual pathway enzymes is the allocation of chorismate to Phe biosynthesis and partitioning of Phe to PAL; chorismate and Phe are branch point intermediates that are substrates for multiple enzymes.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, PAL1 refers to the product encoded by the PAL gene of family I, described by Fukasawa-Akada et al (1996), and PAL2 refers to the product of the PAL gene from family II, as reported by Nagai et al (1994). To determine whether specific forms of PAL are associated with tobacco microsomes, we raised antibodies against synthetic peptide sequences specific for tobacco PAL1, tobacco PAL2, and bean PAL2 (Howles et al, 1996). Soluble and microsomal proteins were isolated from wild-type, PAL-overexpressing (from the bean PAL2 transgene), and PAL-suppressed tobacco stem tissues, subjected to SDS-PAGE, and probed with these antibodies.…”
Section: The Nature Of Pal Associated With Microsomal Membranesmentioning
confidence: 99%
“…These results indicate that externally added unlabeled transcinnamic acid does not dilute isotope incorporation from 3 H-Phe into phenylpropanoid compounds in tobacco cell cultures, whereas externally added unlabeled 4-coumaric acid does, suggesting a specific metabolic compartmentalization of trans -cinnamic acid. This does not directly prove channeling or necessarily indicate the presence of more than one endogenous pool of trans -cinnamic acid in the absence of an externally fed compound.PAL -overexpressing tobacco lines, resulting from constitutive expression of a bean PAL2 gene, overproduce phenylpropanoid compounds (Howles et al, 1996), whereas underexpressing lines, resulting from epigenetic gene silencing (Elkind et al, 1990;Bate et al, 1994), have reduced levels of phenylpropanoid compounds. We initiated callus and then cell suspension cultures from PAL -overexpressing transgenic tobacco; constitutive PAL activities in the cell suspension cultures were at least threefold higher than in comparable cultures derived from wild-type plants.…”
mentioning
confidence: 99%
See 1 more Smart Citation